The anesthetic agent sevoflurane attenuates pulmonary acute lung injury by modulating apoptotic pathways - L. Wang (Brazilian Journal of Medical and Biological Research)
The objective of this study was to evaluate lung protection by the volatile anesthetic sevoflurane (SEVO), which inhibits apoptosis. Male Sprague-Dawley rats (250–280 g; n=18) were randomly divided into three groups. The LPS group received 5 mg/kg endotoxin (lipopolysaccharide), which induced acute lung injury (ALI). The control (CTRL) group received normal saline and the SEVO group received sevoflurane (2.5%) for 30 min after ALI was induced by 5 mg/kg LPS. Samples were collected for analysis 12 h after LPS. Lung injury was assessed by pathological observations and tissue wet to dry weight (W/D) ratios. Apoptotic index (AI) was determined by terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) assay and electron microscopy. Caspase-3 and cleaved-caspase-3 protein levels were determined by immunocytochemistry and western blotting, respectively. Bcl-xl levels were measured by western blotting and Bcl-2 levels by quantitative real-time polymerase chain reaction and western blotting. In the LPS group, W/D ratios, AI values, caspase-3 and cleaved-caspase-3 levels were significantly higher than in the CTRL group and lung injury was more severe. In the SEVO group, W/D ratios, AI, caspase-3 and cleaved-caspase-3 were lower than in the LPS group. Bcl-2 and Bcl-xl expression were higher than in the LPS group and lung injury was attenuated. Sevoflurane inhalation protected the lungs from injury by regulating caspase-3 activation and Bcl-xl and Bcl-2 expression to inhibit excessive cell apoptosis, and such apoptosis might be important in the pathogenesis of LPS-induced ALI.